Investment, ZIS Funds, Mudharabah Financing and Economic Growth in Indonesia - Ichsan Hamidi; Muhammad Farhan; Deassy Apriani (Faculty of Economics and Management, 2024)
This study was conducted to investigate the effect of investment, ZIS funds, and mudharabah financing towards Indonesia’s economic growth during the period 2011-2021. This study uses a quantitative approach with multiple linear regression analysis of monthly time series data. The results showed that investment realization has a positive and significant effect on economic growth, following Schumpeter’s theory which highlights the role of investment in encouraging economic activity. Meanwhile, the distribution of ZIS funds has a positive but insignificant effect on economic growth with 0,7127 p-value, due to a lack of public trust in zakat amil institutions in Indonesia. Which caused a lack of ZIS funds to be distributed in encouraging economic growth. Mudharabah financing also has a positive but insignificant effect on economic growth with 0,5224 p-value, due to a small value of financing and low public interest in applying for mudharabah financing. It is hoped that the results of this study can become a basis for strengthening the role of Islamic economics, especially ZIS and mudharabah towards economic growth in Indonesia and improving people’s welfare.